APPLICATIONS OF IFRS FOR SMALL AND MEDIUM BUSINESS IN THE REPUBLIC OF KAZAKHSTAN - A.A. Kazhmukhametova,; L.Zh. Aitkhozhina,; A.S. Dayrabaeva, (Academic Journal of Physical and Chemical Sciences, 2019)
According to the authors, the development of entrepreneurship is accompanied by the increasing role of accounting information in the areas of management, control and analysis of business activities. The timeliness, quality and accuracy of this information are achieved by a high level of preparedness and professionalism of an accountant. The complexity of applying IFRS for small businesses is also understood by the FCMSU, which has been developing the specialized standard for small-medium business for several years already. Developing a universal standard is a very difficult job, as small business policies and, accordingly, their requirements vary significantly in different countries. Meanwhile, by adopting this standard of the FMSC, it will be possible to maximally incorporate its provisions into the national accounting and financial reporting system.